Maximising the retained value of product cannibalisation based on circular economy principles - Ripant, Eva; Tjahjono, Benny; Fan, Ip-Shing (Cranfield University, 2016)
The maximisation of retained value is one of the determinants in the circular economy that can prolong the product economical and functional values. This paper aims to maximise the retained values of cannibalised products based on the circular economy principles. The approach mainly has been through the desk-based research. The steps to maximise the retained value are developed by adhering to the rules of product cannibalisation and by calculating the retained values. The identification of circular economy principles that is applicable to reverse logistics, particularly product cannibalisation that can contribute to the maximisation retained value process.